Bioethical approach: production of nursing knowledge in Brazil - Faccin Borges, Grasiely (2022)
This article seeks to contribute to critical reflections on the production of nursing knowledge with a bioethical focus in Brazilian publications. This is a literature review conducted by searching the SciELO platform using the descriptors “nursing,” “bioethics” and “ethics,” including articles published between 1999 and 2019. As a result, 43 articles were identified and, after applying inclusion and exclusion criteria, 16 were selected, approaching teaching ethics/bioethics for the nursing course, followed by intensive care/or terminality, organ donation and health care/action/care. A transition in the emerging themes was observed considering the historical context over the years and the interest in the area.